Pathogenic roles of microvesicles in diabetic retinopathy - ZHANG Wei; CHEN Song; Liu Ming-Lin (Acta Pharmacologica Sinica, 2017)
Abstract Diabetic retinopathy (DR) is a common complication of diabetes and has been recognized as the leading cause of blindness in adults. Several interrelated molecular pathways are involved in the development of DR. Microvesicles (MVs) are cell membrane vesicles, which carry many biologic molecules, such as mRNAs, microRNAs, transcription factors, membrane lipids, membrane receptors, and other proteins. They may be involved in intercellular communication that can promote inflammation, angiogenesis, and coagulation. Recent studies have indicated that changes in the number and composition of MVs may reflect the pathologic conditions of DR. At present, MVs are well recognized as being involved in the pathophysiological conditions of tumors and cardio-metabolic diseases. However, the roles of MVs in DR have yet to be investigated. In this review, we provide an overview of DR-induced microvascular injury that is caused by MVs derived from endothelial and circulating cells, and discuss the possible mechanisms by which MVs can lead to endothelial dysfunction, coagulation and inflammation. In addition, the protective effects of preconditioned MVs and stem cell-derived MVs are also described . Understanding the involvement of MVs in the pathophysiological conditions of DR may provide insight into the disease mechanisms and may suggest novel therapeutic strategies for DR in the future.